THE LEVEL OF USING PAYMENT INSTRUMENTS IN THE TRANSFER OF DIGITAL CURRENCY - Nicoleta PANAIT; Mădălina RĂDOI (Challenges of the Knowledge Society)
Globally, in recent years there has been a significant decrease in the number of cash transactions, followed by a decrease in the use of credit cards. Digital payments and e-commerce have undergone tremendous changes, revolutionising the way we buy and pay for various goods and services. E-commerce has ushered in a new era of online shopping, while digital payments have made transactions more convenient, fast and secure. The study analyses the evolution and changes regarding currency transfer, highlighting the importance of cardless digital payments. The convenience, security and cost efficiency they offer have led to their widespread adoption in various industries. The world of digital payments and e-commerce is undergoing rapid transformation, with technological advances and changing consumer behaviour driving the industry's evolution. Recently, especially after the pandemic, there has been a major change in the way people make payments, indicating a clear preference for electronic means, to the detriment of cash. Electronic payments provide full visibility and transparency throughout the entire payment process for both the customer and merchants. It is certain that digital payments and e-commerce will continue to be major drivers of global economic growth and innovation, and the main purpose of digital payments is to increase the convenience, speed and security of conducting financial transactions.